Alternative techniques for the selection of human resources in the field of sport - Mouliá, Patricia I.; Lazzari, Luisa L. (Estudios de Administración, 2010)
The activity of the organizations is a complex phenomenon. Competitive factors are linked to human resources, which makes it necessary for organizations to have specialists in this area.In an uncertain scenario it is desirable to have tools to help make decisions, such as choosing the right candidate for a job. In this article we show three models of human resource selection based on fuzzy set theory and apply them to sports.